Keadilan Sahabat Nabi dalam Perspektif Fuad Jabali - Fadlilah, Nur (Mutawatir, 2012)
Companions of the prophet Muhammad is believed to be the best there ever was Muslim in an Islamic society. The majority of Muslim believe that all the companions of the Prophet is legally fair. The are other views on justice companions into the following categories. a) there is no difference between the companions of the prophet with other Muslim communities whenever and wherever, b) justice companions of the prophet is only given to those who are close to the prophet, and c) justice friends must be determined engagement their slander. Expert hadith of the Prophet, because to save its authentic hadith that the prophet (to be used as evidence in the practice of religious teaching in everyday life) tend to increase the number of friends by creating high standars no to put people into this prestigious group. People Muâtazilah considered reasonable as the most important tool in interpreting revelation. Therefore, the Muâtazilites regard hadith prophet less important than the sense that it tend to limit the number of friends by creating higher standards.It can reduce the number of hadith prophet drastically and educe their role in upholding dogma than sense